The travelling fish bone: Migrated pharyngeal foreign body to the prevertebral muscle - Thomas, Reuben Abraham; Chiun, Kian Chai; Tang, Ing Ping (Egyptian Society of Ear Nose Throat and Allied Sciences, 2017)
Foreign bodies that are impacted in the upper aerodigestive tract are often encountered in a day to day ENT practice. Most of them could usually be removed in a clinic setting but some may require comprehensive imaging and surgery to extricate them. This paper depicts a patient’s self-induced traumatic attempt to remove a huge serrated fish bone that was lodged at the hypopharynx which made its way to the prevertebral soft tissue space compelling an open surgical procedure with neck exploration for definite treatment.